Gallaecia gothica : from the conspiracy of Dux Argimundus (AD 589/590) to integration in the Visigothic kingdom of Toledo. - Cabrera, Rafael B. (Archaeopress Publishing, 2023)
This book uses numismatic and archaeological evidence to offer a new interpretation of the Argimundus rebellion, one of the most difficult challenges of Reccared's reign.